LITERATURE STUDY: THE EFFECT OF INTERACTIVE LEARNING MODELS ON THE COGNITIVE DEVELOPMENT OF ELEMENTARY SCHOOL STUDENTS - Sabrina Salsabila; Imelda Kurniati Siregar; Tiara Sani Sinaga; Yani Lubis (PT Rahis Cendekia Indonesia, 2025)
This study aims to investigate the effectiveness of free educational websites in improving phonological awareness in young children. Using a qualitative-descriptive approach, we analyzed several freely accessible platforms and their use in classroom and home learning settings. Findings show that websites such as Starfall, English Sound, and BBC Learning English contribute positively to children's sound recognition and phoneme segmentation. This study recommends the integration of such tools in the early language curriculum.